Through the lens of Clausewitz’s remarkable trinity and centre of gravity : understanding the cause of the Al Qaeda threat and countering that threat. - Law, Arthur Choong Kian. (2008)
Using Prussian military General Carl Von Clausewitz's two strategic concepts of Remarkable Trinity and the Centre of Gravity, the paper attempts to search for the root causes of the Al Qaeda threat and also gives suggestions as to how counter terrorism efforts can be made more effective.